Awareness Of Sexual Harassment Among Secondary School Students - Dawadi, Sabina; Chaudhary, Tanuja Kumari; Gauro, Pooja (Tribhuvan University Journal, 2022)
Sexual harassment has gained global attention and has been recognized as a critical public health concern with significant negative impacts on victims ‘physical and mental health. This study aimed to find out the awareness of sexual harassment among secondary school students in Nawalparasi District, Nepal. The descriptive cross-sectional research design was used to find out the awareness of sexual harassment among secondary-level students in Devchuli Municipality, Nawalparasi. Students studying in grades eight, nine, and ten were identified from two conveniently selected schools out of the 12 private schools in the study area. In total, 150 students took part in the study, and every one of them completed the questionnaire in its entirety. Data entry and analysis were done in Statistical Package for Social Science (SPSS) version 20. The obtained data we reanalyzed using descriptive statistical methods like frequency, percentage, mean, and chi-square to ascertain the relationship between the level of awareness of sexual harassment and the selected socio-demographic characteristics. The findings showed that, among 150 respondents, most (82.0%) had a good level of awareness regarding sexual harassment. According to respondents ‘suggestions for preventing sexual harassment (SH) can be stopped by enacting strict rules, regulations, and policies against those who engage in the practice (85.3%), running awareness campaigns about the issue (83.3%), and offering training on how to handle sexual harassment (75.3%).There was no statistically significant relationship between the level of awareness of sexual harassment and the selected socio-demographic variables. It can be recommended that schools conduct an ongoing sensitization program or awareness campaign to teach students about sexual harassment periodically.